Implementasi Edukasi Kesehatan untuk Meningkatkan Self Efficacy dan Motivasi pada Pasien Hipertensi: Implementation of Health Education to Improve Self-Efficacy and Motivation in Hypertension Patients - Salami, Salami; Wilandika, Angga; Sukmayanti, Maya; Enisah, Enisah; Mulyani, Delia Rida (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Hypertension is a significant contributor to the leading cause of death in Bandung City. This chronic condition requires long-term management by individuals to prevent potentially fatal complications. Therefore, it is crucial for individuals with hypertension to actively engage in the management of their condition, which demands high levels of motivation and self-efficacy. In this context, health education is pivotal in empowering patients to perform self-care effectively. This community service (Pengmas) activity was conducted within the jurisdiction of the Cijagra Lama Health Center in Bandung City, and integrated into the Ners professional student program, on May 19, 2024. The community service involved providing educational materials on hypertension and its management. The educational approach included presentations using PowerPoint slides and the distribution of informational leaflets. Results from pre- and post-test with the Wilcoxon test demonstrated a significant improvement in both self-efficacy and motivation among the 39 participants in the community service program, concerning the management of hypertension. This initiative is expected to enhance participants' ability to manage their condition effectively, promoting better control over their health.